Factors associated with stroke among adult patients with hypertension in Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia, 2018: A case-control study - Mekonen, Haftea Hagos (PLoS One, 2020)
BACKGROUND: Globally, the burden of stroke is increasing at an alarming rate. Factors associated with stroke among hypertensive patients are not consistent across different studies and there are limited studies particularly to hypertensive stroke in the particular setting. This study aimed to assess factors associated with stroke among patients with hypertension in Ayder Comprehensive Specialized Hospital, Mekelle, Tigray, Ethiopia, in 2018. METHODS: Hospital-based case-control study was conducted from February to April 2018. Cases were adult hypertensive patients with stroke and controls were adult hypertensive patients without a stroke. Cases and controls were identified from the patient’s card review. Using a systematic random sampling technique 89 cases and 356 controls were included in this study. Record review, physical measurement, and interview techniques were used to collect data. Data was entered and analyzed by using SPSS version 23. Variables with a p-value of less than 0.25 in the bivariate logistic regression were selected for multivariable logistic regression. The adjusted odds ratio and 95% confidence interval were used to determine the association. P-value <0.05 was used to declare statistical significance. RESULTS: The mean age of cases and controls were 56.3 years (SD±13.53) and 51.9 years (SD±12.67) respectively. Lost to follow-up (AOR = 2.474, 95%CI: 1.368–4.929), alcohol drinking (AOR = 2.440, 95%CI: 1.291–4.613), use of excessive salt in diet (AOR = 3.249, 95%CI: (1.544–6.837), medication non-adherence (AOR = 3.967, 95%CI: 2.256–6.973), uncontrolled systolic blood pressure, (AOR = 3.196, 95%CI: 1.60–6.382), uncontrolled diastolic blood pressure (AOR = 2.204, 95%CI: 1.130–4.297) and high cholesterol level (AOR = 2.413, 95%CI: 1.319–4.414) were found to be significant factors. CONCLUSION: Lost to follow-up, alcohol drinking, uses of excessive salt in diet, medication non-adherence, and uncontrolled systolic and diastolic blood pressure were associated with stroke. Health education on lifestyle practices and hypertension-related complications in each follow-up visit is very essential for improving the primary stroke prevention.